2006
DOI: 10.1021/jm060768f
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of New Cyclic Melanotropin Peptide Analogues Selective for the Human Melanocortin-4 Receptor

Abstract: Intensive efforts have been made to develop potent and selective ligands for certain human melanocortin receptors as possible treatments for obesity and sexual dysfunction due to the role of these receptors in feeding behavior, energy homeostasis, sexual function, etc. A number of novel α-MSH analogues were designed and synthesized primarily on the basis of our previous MTII NMR structure. In these peptide analogues, a disulfide or lactam bridge between residues at positions 5 and 8 was used as a conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 61 publications
4
31
0
1
Order By: Relevance
“…[2][3][4][5][6][7] Adding constraint can improve target selectivity; namely, favoring the binding to one protein or receptor over others that share a high degree of homology or ligand recognition properties. [8][9][10][11][12] This is closely aligned with another advantage, the potential for establishing the bioactive conformation of the unconstrained parent compound. [13][14][15] In the case of peptide and peptidomimetic structure, additional reported benefits of adding organic constraints or effecting cyclization include increased resistance to proteases and in vivo metabolic stability, [16][17][18][19][20][21][22][23] as well as improved cell membrane permeability [24][25][26][27][28][29] (although the latter may be a contingent rather than a necessary property of cyclic peptides 30,31 ).…”
Section: Conformational Constraint In Protein Ligand Design and The Imentioning
confidence: 92%
“…[2][3][4][5][6][7] Adding constraint can improve target selectivity; namely, favoring the binding to one protein or receptor over others that share a high degree of homology or ligand recognition properties. [8][9][10][11][12] This is closely aligned with another advantage, the potential for establishing the bioactive conformation of the unconstrained parent compound. [13][14][15] In the case of peptide and peptidomimetic structure, additional reported benefits of adding organic constraints or effecting cyclization include increased resistance to proteases and in vivo metabolic stability, [16][17][18][19][20][21][22][23] as well as improved cell membrane permeability [24][25][26][27][28][29] (although the latter may be a contingent rather than a necessary property of cyclic peptides 30,31 ).…”
Section: Conformational Constraint In Protein Ligand Design and The Imentioning
confidence: 92%
“…The binding affinity and the AC activity of the peptides under investigation were evaluated for the various human MCRs. Peptide 8 was characterized by a good binding affinity toward the hMC4R (IC 50 5 1.8 nM) without exhibiting any affinity for the other MCR subtypes up to 10 À5 M. 197 Worth noting, the compound behaved as an antagonist with a 50% binding efficiency when compared with that of the reference melanocortin receptor agonist MTII. Thus, the authors suggested an allosteric molecular interaction between 8 and the hMC4R, which was corroborated by assaying MTII in the presence of antagonists.…”
Section: Melanocortin Receptorsmentioning
confidence: 99%
“…However, the allosteric modulation of MCRs by exogenous ligands has been evidenced only within a small group of conformationally constrained peptides, exemplified by compound 8 (Fig. 9), 197 designed and tested following a structural NMR study on cyclic melanocortin agonists and antagonists. The binding affinity and the AC activity of the peptides under investigation were evaluated for the various human MCRs.…”
Section: Melanocortin Receptorsmentioning
confidence: 99%
“…Recently, we have discovered allosteric ligands for the hMC4R ( 25 and 26 , Table 4) [65]. These ligands were designed as structural analogs with the arginine side chain moiety in different relationships to the other pharmacophore side chain groups for the MCRs [65].…”
Section: Hmc4r Antagonistsmentioning
confidence: 99%